Korelasi antar Karakter Hasil Lima Varietas Tanaman Kacang Panjang (Vigna sinensis) di Lingkungan Organik - Putra, Dio Anugrah; Wibowo, Lestari; Ginting, Yohanes Cahya; Sa'diyah, Nyimas (Universitas Lampung, 2024)
This study aims to determine the correlation between the yield characteristics of the yard long bean yield, and the superiority of one of the varieties in an organic environment. This research was conducted at the Integrated Field Laboratory and Seed and Plant Breeding Laboratory, Faculty of Agriculture, University of Lampung in July 2021 – November 2021. This experiment was arranged in a Completely Randomized Design (CRD) with 3 replications and then continued with data analysis in the form of linear analysis, analysis of diversity , and significance test. The observed variables included flowering age, pod color, pod harvesting age, pod length, pod diameter, number of seeds per pod, sugar content, number of productive branches, number of good pods, total number of seeds, and distance between locules. The results showed that the pod length and the number of seeds per pod (r = 0.66). Total pod weight was positively correlated with the number of productive branches (r = 0.83), the number of good pods (r = 0.96), and the total number of pods (r = 0.96). The number of productive branches correlated positively with the number of good pods (r = 0.87) and the total number of pods (r = 0.86). The number of good pods variable has a positive correlation with the total number of pods (r = 0.98). The Cantonese Tavi variety has an advantage in the number of good pods produced in an organic environment. Keywords: Correlation, Organic Environment.